Thiamine-Responsive Acute Pulmonary Hypertension of Early Infancy (TRAPHEI)-A Case Series and Clinical Review - Nalinikanta Panigrahy; Dinesh Kumar Chirla; Rakshay Shetty; Farhan A. R. Shaikh; Poddutoor Preetham Kumar; Rajeshwari Madappa; Anand Lingan; Satyan Lakshminrusimha (MDPI AG, 2020)
Persistent pulmonary hypertension of the newborn (PPHN) is a syndrome of high pulmonary vascular resistance (PVR) commonly seen all over the world in the immediate newborn period. Several case reports from India have recently described severe pulmonary hypertension among infants in the postneonatal period. These cases typically present with respiratory distress in 1-6-month-old infants, breastfed by mothers on a polished rice-based diet. Predisposing factors include respiratory tract infection such as acute laryngotracheobronchitis with change in voice, leading to pulmonary hypertension, right atrial and ventricular dilation, pulmonary edema and hepatomegaly. Mortality is high without specific therapy. Respiratory support, pulmonary vasodilator therapy, inotropes, diuretics and thiamine infusion have improved the outcome of these infants. This review outlines four typical patients with thiamine-responsive acute pulmonary hypertension of early infancy (TRAPHEI) due to thiamine deficiency and discusses pathophysiology, clinical features, diagnostic criteria and therapeutic options.